Acrylamide Formation and Different Mitigation Strategies during Food Processing – A Review. Issue 1 (2nd January 2022) - Maan, Abid Aslam; Anjum, Muhammad Adeel; Khan, Muhammad Kashif Iqbal; Nazir, Akmal; Saeed, Farhan; Afzaal, Muhammad; Aadil, Rana Muhammad
ABSTRACT: Thermal treatment can initiate the production of some undesirable compounds in foods during processing. Acrylamide is one among such compounds that is produced (in starch-rich foods) as a result of Maillard reaction between reducing sugars and free amino acids. Acrylamide has gained much attention owing to its wide occurrence, dietary exposure, and toxicity. Its formation mechanism and mitigation has been an area of interest for numerous researchers since its discovery in foods. Some reviews have already been published on acrylamide where its formation and mitigation has been discussed with reference to some specific group of foods and/or some specific mitigation technique. In others, the mitigation section does not cover all the aspects of acrylamide attenuation reported in the literature. The present paper provides the updated and comprehensive information on formation, occurrence, dietary exposure, toxicity, and mitigation of acrylamide in foods during processing.